2020
DOI: 10.1109/access.2020.3028856
|View full text |Cite
|
Sign up to set email alerts
|

Low-Voltage Capacitive-Based Step-Up DC-DC Converters for RF Energy Harvesting System: A Review

Abstract: Bulky off-chip inductors are predominantly adopted for inductive-based step-up DC-DC converter in RF energy harvesting (RFEH) systems, which impose a restriction in physical form factor for miniaturized device. This paper review and explores the capacitive-based step-up DC-DC converters (charge-pump) as voltage boosting element for low-voltage RFEH systems. An overview of RFEH is established and a comprehensive review of CMOS charge-pump is followed along with the complementary frequency generation circuit use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 99 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…The switching loss is negligible when the switching frequency of the footer transistor is lower than the resonant frequency [5]. Also, appropriate sizing of PMOS and NMOS alleviates the tradeoff between switching and conduction loss at a ratio of 2:1 [43]. Proper gate biasing techniques assist in forward conduction and leakage loss [44], [45].…”
Section: B Power Losses Reduction and Optimizationmentioning
confidence: 99%
“…The switching loss is negligible when the switching frequency of the footer transistor is lower than the resonant frequency [5]. Also, appropriate sizing of PMOS and NMOS alleviates the tradeoff between switching and conduction loss at a ratio of 2:1 [43]. Proper gate biasing techniques assist in forward conduction and leakage loss [44], [45].…”
Section: B Power Losses Reduction and Optimizationmentioning
confidence: 99%
“…Consequently, the proposed CP consists of a stand-alone boosted driver circuit to solve the above-mentioned issue as an alternative to other competitive techniques with different primary purposes in relation to ultra-low voltage research area (e.g., a clock booster based driver, topology reconfiguration approach, implementation of adiabatic principle and many others [ 10 , 24 , 25 ]. The transistor level schematics of the proposed driver and detailed cross-connection with a complementary replica circuit are shown in Figure 3 and Figure 4 , respectively.…”
Section: Dc-dc Converter Systemmentioning
confidence: 99%
“…According to the state-of-the art, the RF-EH systems dominantly employ inductive DC-DC converters. These are more attractive compared to the capacitive counterparts (charge pumps) due to the higher power conversion efficiency (PCE) and suitability for low-voltage start-up [ 10 ]. Recent research has revealed that the charge pump-based step-up converters reach improved PCE and start-up ability [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of converting energy from ambient sources into electrical energy is called Energy Harvesting (EH) [14]. Some examples of available ambient sources of energy are electromagnetic radiation (such as light [15], [16], and Radio Frequency (RF) waves [17], [18], thermal gradients [19], and mechanical motion [20]).…”
Section: Introductionmentioning
confidence: 99%